(untitled) (Nigerian Journal of Physiological Sciences, 2022)
Diabetes mellitus is one of the most widespread diseases affecting the world’s population causing substantial morbidity, mortality and long-term complications. This study was designed to investigate possible hypoglycemic, hypolipidemic and antioxidant effect of ethanolic stem bark extract of Anacardium occidentale in streptozotocin (STZ)-induced diabetic rats. Twenty-eight STZ (60 mg/kg body weight)-induced diabetic, male albino rats were randomly distributed into Groups II-V (7 rats each) and orally administered with water, metformin (14.2 mg/kg), 200 mg/kg Anacardium occidentale extract and 400 mg/kg Anacardium occidentale extract respectively daily for 15 days. Group I rats were untreated with STZ and serves as control all under the same sham handling. Blood samples were taken for measurement of fasting blood glucose (FBG) and lipid profile. Liver and kidney tissue samples were taken for determination of glycemic indices (glucose and glycogen), as well as redox status markers such as malondialdehyde (MDA), total glutathione (GSH), activities of superoxide dismutase (SOD) and glutathione-s-transferase (GST). Results showed that treatment with 200 and 400 mg/kg Anacardium occidentale stem bark extract reversed hyperglycemia and hyperlipidemia induced by STZ similar to what was observed with the standard drug, metformin. Similarly, both extract concentration produced a significant reduction in MDA while the activity of SOD and GST, as well as concentration of GSH were elevated. This study suggested that ethanolic stem bark extract of Anacardium occidentale at 200 and 400 mg/kg can ameliorate diabetes and its associated complications via its hypoglycemic, hypolipidemic, antioxidant and free radical scavenging properties